2004
DOI: 10.1023/b:pres.0000028337.72340.3a
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Photosystem I and Photosystem II in Wheat Seedlings with their Root–shoot Transition Zones Exposed to Red Light

Abstract: The present study was conducted to observe the role of the root-shoot transition zone in the development of PS I and PS II in red light. The development of PS II and PS I was severely inhibited when root-shoot transition zones of wheat seedlings were exposed to red light (670 nm) of intensity 500 micromol m(-2) s(-1). Chlorophyll biosynthesis was also inhibited in these seedlings. Most of the PS I and PS II proteins (D1, LHCPII, CP47, OEC33) and their transcript levels were severely inhibited but cyt b6f compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 24 publications
0
19
0
Order By: Relevance
“…1). Most of the enzymatic activities, involved in Chl biosynthesis and greening process, are impaired in seedlings grown in red light having their shoot bottom exposed (Sood et al 2005;Sood et al 2004). Suppression of photomorphogenesis by red light (400 μmol photons m −2 s −1 ) is a red-HIR response of PhyA (Roy et al 2013).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1). Most of the enzymatic activities, involved in Chl biosynthesis and greening process, are impaired in seedlings grown in red light having their shoot bottom exposed (Sood et al 2005;Sood et al 2004). Suppression of photomorphogenesis by red light (400 μmol photons m −2 s −1 ) is a red-HIR response of PhyA (Roy et al 2013).…”
Section: Discussionmentioning
confidence: 99%
“…In previous studies, we have shown rice and wheat seedling grown with their shoot bottom exposed to constant red light or when given in the form of light-dark cycles do not accumulate chlorophyll (Chl) (Gupta et al 2010;Roy et al 2013;Sood et al 2005;Sood et al 2004;Tripathy and Brown 1995). Red light perceived by the shoot bottom downregulates the protein and gene expression of the enzymes involved in the biosynthesis of tetrapyrroles (Sood et al 2005;Sood et al 2004;Tripathy and Brown 1995).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Table 3. Comparison of the spectral heterogeneity of the non-photoactive and photoactive protochlorophyllide pools observed in etiolated bean leaves , during greening (Amirjani and Sundqvist 2004), and in red-radiation-grown wheat (Sood et al 2004 Sood et al (2004) studied the effect of irradiation of the root-shoot transition zone on the accumulation of Pchlide in leaves in red-radiation-grown wheat (500 µmol m -2 s -1 , wavelength = 670±26 nm). The leaves from plants with an irradiated root-shoot transition zone differed from those which zone was not irradiated, by the absence of the spectral bands corresponding to photosystems in fluorescence spectra.…”
Section: Chl Synthesis During Greening and In Green Plantsmentioning
confidence: 99%
“…We found that the chlorophyll fl uorescence parameters of the chrysanthemum leaves were not linearly correlated with the R:FR ratios. Th e eff ects of R:FR ratios on the fl uorescence parameters may be related to the balance between PSI and PSII (Sood et al 2004).…”
Section: Th E Chl a Contents And Spad Values Of Chrysanthemu M Leavesmentioning
confidence: 99%